(untitled) (Iter, 2022)
This article intends to demonstrate the way Plato’s position regarding the relation between φύσις and ἦϑος, as well as the role of ἰδέαι in it, constitutes a revolution of the sense in which that relation had beed conceived until then. The first three sections present some passages of Heraclitus and Parmenides regarding ἦϑος and justice (δίκη), with the help of some poetic texts. This results in an outline of the archaic notion of ἦϑος and φύσις, according to which justice constitute an ordering of the κόσμος as a whole. The two following sections show the main characteristics of Plato’s ἰδέαι, emphasizing the ἰδέα of Good and the importance of the notion of δύναμις. From this standpoint the foundation of the πόλις proposed in the Republic is presented, in order to observe the passage from a cosmic justice to a notion that considers it as a guiding principle for beings that act according to their ἦϑος and as a measure that transcends all being, given that it is an ἰδέα.